Primary care patients with cardiovascular disease eligible for nurse‐led internet‐based cognitive behavioural therapy for insomnia: Characteristics and motives for participation - Sandra Öberg; Linda Johansson; Mattias Georgsson; Jonas Sandberg; Anders Broström (Wiley, 2023)
Abstract Aim To describe demographic, physical and psychological characteristics associated with insomnia in patients with cardiovascular disease (CVD) participating in nurse‐led Internet‐based cognitive behavioural therapy for insomnia (I‐CBTI), and their motives and expectations regarding participation in I‐CBTI. Design A mixed method design was applied, including primary care patients with angina pectoris, myocardial infarction, heart failure, atrial fibrillation and atrial flutter or arrhythmia in southern Sweden. Methods Data on demographics, insomnia severity and physical and psychological characteristics were collected through self‐rated validated questionnaires (n = 126). Motives and expectations were collected through interviews (n = 19) and analysed using the 'personas' model. Results Physical symptoms and psychological characteristics were associated with insomnia. Three personas were identified: the pragmatist (a curious and optimistic persona), the philosopher (a problem‐solving persona) and the philanthropist (an altruistic persona). Expectations were positive among the three personas, but comorbid conditions reduced the perceived ability to make necessary behavioural changes.